Pengaruh Gaya Kepemimpinan, Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Pegawai - jaini Rahman; Hadi Sunaryo; Budi Wahono (E-JRM : Elektronik Jurnal Riset Manajemen, 2020)
Abstract  This study aims to find out and analyze the influence of leadership style, work motivation and work discipline on the performance of the malang city environment office staff. The population in this study amounted to 207 and the sample taken amounted to 69 respondents. Data collection through questionnaire distribution. Data analysis in this study used spss version 16. The sampling technique uses quantitative methods and the data testing techniques used are validity test, class assumption reliability test, multiple linear regression test and hypothesis test. The analysis shows that leadership style, work motivation and work discipline simultaneously have an influence on employee performance, partially leadership style and work motivation have no effect, but work discipline has an influence on employee performance of employees of the office of the city of malang. Keywords: Leadership Style, Motivation, Work Discipline And Performance